Market orientation of Islamic banks in the UAE: an empirical examination. (10th June 2020) - Anwar, Syed Aziz
Market orientation of Islamic banks is an area of optimal managerial relevance that has not been subjected to a rigorous examination in the literature. Because market orientation addresses how organisations adapt or should adapt to their environment to stay competitive, Islamic banks cannot afford to neglect market-oriented strategies to improve performance. Therefore, this paper makes a modest attempt to examine market orientation of Islamic banks operating in the robust international banking sector of the UAE. This kind of research exercise is anchored in an extensive review of the market orientation literature, pooling together previously disparate strands of knowledge. Empirical evidence is presented and managerial implications are also discussed.